Clinical study of patient with Ankylosing Spondylitis - Lee Jae-Min; Hong Kwon-eui (Korean Pharmacopuncture Institute, 2006)
Object : This study is designed in order to evaluate oriental medical treatment of ankylosing spondylitis. Methods : The authors observed patient by ROM & VAS for operated acupuncture treatment, herbal medicine treatment and physiotherapy Conclusion : 1. Ankylosing spondylitis patient of this case is caused by taiyang channel warm-heat evi. 2. Ankylosing spondylitis patient by taiyang channel warm-heat evi is evaluated by acupuncture treatment. ; SP3, S36, LIll, LI4, S40. 3. Ankylosing spondylitis patient by taiyang channel warm-heat evi is evaluated by Hervbal medication. ; Gamikangwhalsungsub-Tang.